Analysis of immunogenicity and purification methods in conjugated polysaccharide vaccines: a new approach in fighting pathogenic bacteria - Sheikhi, Arya; Shirmohammadpour, Mina; Mahdei Nasirmahalleh, Nima; Mirzaei, Bahman (Frontiers in Immunology, 2024)
Carbohydrates are commonly found in conjunction with lipids or proteins, resulting in the formation of glycoconjugates such as glycoproteins, glycolipids, and proteoglycans. These glycoconjugates are essential in various biological activities, including inflammation, cell-cell recognition, bacterial infections, and immune response. Nonetheless, the isolation of naturally occurring glycoconjugates presents challenges due to their typically heterogeneous nature, resulting in variations between batches in structure and function, impeding a comprehensive understanding of their mechanisms of action. Consequently, there is a strong need for the efficient synthesis of artificial glycoconjugates with precisely described compositions and consistent biological properties. The chemical and enzymatic approaches discussed in this paper present numerous research opportunities to develop customised glycoconjugate vaccines.